Analysis of E-textbooks: Development, use and availability on the Slovenian Market - Stanković Elesini, Urška; Tomažin, Grega (Journal of Graphic Engineering and Design, 2018)
Through several projects in Slovenia, e-learning materials have been developed over the last decade, with some primary and secondary schools already using them successfully in their educational processes for several years. The objectives of this research were to analyse the development of e-learning materials, in particular the process of creating e-textbooks, to identify experiences in the use of e-learning materials and to determine their availability on the market. In order to understand the development process, our research involved the creation of i-textbooks. The problems we encountered during the creation of i-textbooks are presented in this article. The results showed that teachers are satisfied with the use of previously developed e-learning materials. They also agreed that traditional textbooks cannot be replaced completely by e-textbooks. However, they do represent an important motivation tool that assists them in facilitating the transfer of knowledge and helps learners to better understand and learn the contents of different subjects. The e-learning materials present on the Slovenian market are freely accessible or require payment, depending on the editor. A great deal of e-learning materials is also inactive, as was emphasised in our research.